THE INFLUENCE OF JOB SATISFACTION AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE IN CV. PUTRI SION TUNGGUNJAGIR VILLAGE, MANTUP SUB-DISTRICT, LAMONGAN - Nurul Badriyah (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
The development of the business world today more rapidly resulting in tight competition. This is demanding business players in order to leap ahead of the competition with how to improve the quality of human resources and expected employee can improve performance. To be employee performance and the company is also required to pay attention to the factors that can affect the performance of the employees. This research is a type of quantitative research, data obtained with the spread of the questionnaire to 45 respondents. The population in this research is all employees on CV. Putri Sion which numbered 45 people. The Data obtained and then in the analysis using the validity test, test reliability test, classical assumptions, determination coefficient test, t test, F test and multiple linear regression analysis. This research result shows that partially, job satisfaction and leadership style significantly affect to employee performance meanwhile the most dominant affecting performance is employee jobs satisfaction.